Types of American Labor Unions–The Musicians of St. Louis and New York - Commons, John R. (Quarterly Journal of Economics, 1906)
Journal Article Types of American Labor Unions. — The Musicians of St. Louis and New York Get access John R. Commons John R. Commons University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 20, Issue 3, May 1906, Pages 419–442, https://doi.org/10.2307/1882857 Published: 01 May 1906